Building Students' Interaction by Using Talking Chips Technique: A Classroom Action Research - Warahuwena, Susan; Rijoly, Helena M. (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2021)
This study focuses on building students' interaction by using the talking chips technique, and it aims to find out how the talking chips technique can be applied to build students' interaction and describe the responses toward the implementation of this test of this research was students of SMA Negeri 14 Ambon consisting of 26 students (4 groups) in XI-Science class. The data was collected from classroom observation, weekly observation, and questionnaires. The design was classroom action research. The study concludes that this technique is successfully applied to build students' interaction, and the students have a positive response towards the implementation of this technique. Applying the Talking Chips technique in the learning-teaching process gives students more opportunities to be actively involved and work cooperatively in learning activities. This technique also motivates students to speak or express their ideas; therefore, it has a good impact on the students in building their interaction in the classroom.